Capturing differences in perception and aesthetic judgment of live or medially presented music: development of a self-report instrument - Meinel, Larina Sue; Bullerjahn, Claudia; Lindau, Alexander; Wald-Fuhrmann, Melanie (Frontiers in Psychology, 2024)
Nowadays there are multiple ways to perceive music, from attending concerts (live) to listening to recorded music through headphones (medial). In between there are many mixed modes, such as playback performances. In empirical music research, this plurality of performance forms has so far found little recognition. Until now no measuring instrument has existed that could adequately capture the differences in perception and aesthetic judgment. The purpose of our empirical investigation was to capture all dimensions relevant to such an assessment. Using 3D-simulations and dynamic binaural synthesis, various live and medial situations were simulated. A qualitative survey was conducted at the Department of Audio Communication of the Technical University of Berlin (TU Berlin). With the help of the repertory grid technique, a data pool of approximately 400 attribute pairs was created and individual rating data were collected. Our first study served to create a semantic differential. In a second study, this semantic differential was evaluated. The development of the semantic differential was carried out by first using a mixed-method approach to qualitative analysis according to grounded theory. Thereafter, a principal component analysis reduced the attribute pairs to 67 items in four components. The semantic differential consists of items concerning acoustic, visual and audio-visual interaction as well as items with an overarching assessment of the stimuli. The evaluation study, comprising 45 participants (23 male and 22 female, M = 42.56 years, SD = 17.16) who rated 12 stimuli each, reduced the items to 61 and resulted in 18 subscales and nine single items. Because the survey used simulations, the social component may be underrepresented. Nevertheless, the questionnaire we created enables the evaluation of music performances (especially for classical concerts) in a new scope, thus opening many opportunities for further research. For example, in a live concert context, we observed not only that seating position influences the judgment of sound quality but also that visual elements influence immersion and felt affect. In the future, the differential could be reviewed for a larger stimulus pool, extended or used modularly for different research questions.